Analisis Tingkat Penerimaan Tentang Penerapan Industri Hijau Pada Peraturan Pemerintah Sebagai Bentuk Eko-Efisiensi Dalam Meningkatkan Kinerja Hijau - Wenti Ayu Sunarjo; Maghfiroh; Nur Susanti; Muhammad Milzam; Nur Ermawati; Yovita Christi; Alilisa Rahmawati (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
Implementing eco-efficiency in the batik industry is important considering the currently developing environmental problems. In order to realize a sustainable batik industry with green performance, an analysis was carried out on the level of acceptance of applicable government regulations in order to change towards an independent green industry. In line with the research objective, it is to analyze the level of income of the batik industry regarding the implementation of government regulations relating to the green industry through the application of eco-efficiency in order to measure green performance in the batik industry. Through a survey method carried out on all batik industries by taking random samples from 500 batik industries in Pekalongan City. The research results show that for all respondents' answers to each question item, the results obtained were an average of 66.25% of batik industry players who had accepted the existence of a green industrial policy for the batik industry in accordance with the regulations stipulated in PERMENPERIN No. 10 of 2023. It appears as supporting data that results show that 60% of batik business actors also received training for the batik industry which has not received the title as a green industry.